Dominant Factor Affecting PHBS at Household in Padang - Ringga Rahmi Prima; Melinda Noer; Benny Hidayat (Jurnal Kesehatan Masyarakat Andalas, 2017)
Healthy and clean behaviour are behaviors that made family contribute in pursuing a healthy living environment. Based on City Health Office Padang data in 2015, the implementation of healthy and clean behavior at Andalas Public Health Center work area only 3,18 %. The Purpose of this study to determine the factors associated with the implementation of Healthy and clean behaviour among household  who live in Padang. This research use mixed method design with sequential explanatory approach. Samples were choosen using cluster sampling technique amount 99 unit of Household. The quantitative data were collected by interview with questionare and analyzed using multivariate, logistic regression with 95% CI (p= 0.05). The qualitative data were collected by depth interview and analyzed using content analysis. The result of multivariate analysis showed the dominant factor is basic sanitation. Basic sanitation eligible households will increase by 5.8 times. The research suggest Public Health Center should build cooperation cross-sectors with Public Work Service Office to fulfill of basic sanitation, like the fulfill of clean water needs and adding healthy sewerage system